White-fronted Goose statistics, 1952-53 - Boyd, Hugh (Wildfowl, 1953)
The collection of data on the composition of the Whitefront population by the methods described in the Fifth Annual Report (pp. 14-19) was continued and extended in 1952-53. New sources of information included the identification of geese ringed in earlier years and counts of the numbers of single adults. The principal results are: (1) the mean proportion of first-winter birds in 1952-53 was 33%, a figure similar to those obtained in the two preceding winters; (2) the mean brood-size was 3.18, less than in 1951-52 but greater than that in 1950-51; (3) 6.0% of families were accompanied by only one parent; (4) only 2.2% of first-winter birds were not in family parties; (5) estimates of the survival factor from observations of ringed geese suggest that about forty of every hundred geese alive at 1 January die before the following 1 January; (6) analysis of the composition of the adult population indicates that the proportion of second- and third-winter birds is increasing, or the proportion of older birds decreasing, a condition characteristic of a growing population; (7) it is shown that many second-winter birds were paired, although no birds less than 3 years old are known to have been parents.